1974
DOI: 10.1136/bmj.1.5906.477
|View full text |Cite
|
Sign up to set email alerts
|

Experience in Monitoring Gentamicin Therapy during Treatment of Serious Gram-Negative Sepsis

Abstract: SummaryThis paper reports our experience in monitoring gentamicin therapy during the treatment of 68 episodes of serious Gramnegative sepsis in 65 hospital patients. Most of the patients had major underlying disease. Of those who were adequately treated (peak serum concentrations of 5 ,ug/ml or more in 72 hours for septicaemia, urinary tract infection, and wound infection; and 8 ,ug/ml or more at some time during the course of treatment for pneumonia) B4% (46 out of 55) were cured. These serum concentrations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
1
3

Year Published

1979
1979
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(116 citation statements)
references
References 10 publications
(7 reference statements)
4
108
1
3
Order By: Relevance
“…A favourable outcome was also demonstrated in patients with gram-negative pneumonia who achieved maximum peak concentrations of gentamicin or tobramycin of > 7mg 1' or mean peak concentrations of > 6 mg l- (Moore et al, 1984b). Other studies support these findings and suggest that peak concentrations should not be < 5 mg 1-1, and preferably much higher (Noone et al, 1974, Moore et al, 1987.…”
Section: Introductionsupporting
confidence: 64%
“…A favourable outcome was also demonstrated in patients with gram-negative pneumonia who achieved maximum peak concentrations of gentamicin or tobramycin of > 7mg 1' or mean peak concentrations of > 6 mg l- (Moore et al, 1984b). Other studies support these findings and suggest that peak concentrations should not be < 5 mg 1-1, and preferably much higher (Noone et al, 1974, Moore et al, 1987.…”
Section: Introductionsupporting
confidence: 64%
“…Frequently the doses required initially are 1.5 to 3 times the normal recommended dosage (Zaske et al, 1982a;Denaro & Ravenscroft, 1987). Retrospective studies have suggested an improved survival with such a stratagem (Noone et al, 1974;Zaske et al, 1982b;Moore et al, 1984a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Aminoglycoside pharmacokinetic parameters may be greatly changed in patients who are seriously ill with septicaemia and/or have large fluctuations in their extra-cellular fluid volume (Pennington et al, 1975;Zaske et al, 1976;Denaro & Ravenscroft, 1987;Lacarelle et al, 1987). The importance of the correlation between peak serum aminoglycoside concentrations and clinical outcome is now widely accepted (Jackson & Riff, 1971;Noone et al, 1974;Moore et al, 1984a,b). Methods used to individualize therapy must (1) accurately estimate volume of distribution (V) and clearance (CL), so that desired peak drug concentrations are attained, (2) have the ability to predict changes in aminoglycoside pharmacokinetic parameters that occur with disease, (3) be easily implemented and (4) be cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic gentamicin concentrations in humans were been established by Barza et al 12 and Noone et al 13 as 5-10 mg/mL. Persistent concentrations higher than 10 mg/mL lead to alterations in the VIII craneal nerve and nephrotoxicity, although lower levels may also be associated with toxic effects.…”
Section: Discussionmentioning
confidence: 99%